Implementation of Digital Marketing at Printing Company to Increase Customer Acquisition and Customer Retention (Case Study: Citra Kreasindo Mandiri Company) - Clairine Irawan; Budi Susanto; Rismi Juliadi (Conference Series, 2020)
In facing the global change and technology, PT Citra Kreasindo Mandiri company needs to make a change in the form of the application of technology within the company. The data was collected qualitatively by conducting interviews with business people involved, it’s the business owners and employees of PT Citra Kreasindo Mandiri so that data was obtained about current business conditions in terms of strategy, technology, customers, organization and culture and operations. Business priority is in the marketing section which is the sub-dimension of the strategy dimension. From this condition, one of the strategies that can be done is to implement digital marketing at the company PT Citra Kreasindo Mandiri The application of digital marketing is carried out to increase the customer acquisition rate and customer retention rate. The analysis technique is performed by comparing the company's business capabilities with the company's gap analysis. The results given from the application of digital marketing are that companies have the ability to be able to carry out digital transformation and the application will have a positive influence on the customer acquisition rate, customer retention rate and also company revenue.